1999
DOI: 10.1109/61.736713
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a silicone-based coating in a substation application

Abstract: silicone rubber coating applied to insulators in rd located near Long Island Sound has depolymerized and become putty-like after six years of service. Coating samples were taken from high creep insulators which were energized and weathered, weathered but not energized, and neither weathered or energized (warehouse storage). The unweathered and unenergized coating did not appear to degrade. The weathered but unenergized coating had degraded measurably but was still in an operational state. The energized and wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…One sample (energized RTV) was taken from the coating surface of a porcelain insulator which had been energized for over seven years at a system voltage of 345 kV in a switchyard along the CT coast of Long Island Sound, USA [9]. Fig.…”
Section: B Sample Preparationmentioning
confidence: 99%
“…One sample (energized RTV) was taken from the coating surface of a porcelain insulator which had been energized for over seven years at a system voltage of 345 kV in a switchyard along the CT coast of Long Island Sound, USA [9]. Fig.…”
Section: B Sample Preparationmentioning
confidence: 99%
“…According to a field measurement in a 230 kV high voltage substation, the acid rain has a pH of 3.9 [3]. By comparing the weight loss of field aged RTV samples to laboratory aged samples, this study suggested that one month of immersion in nitric acid of pH=3.9 at 90 0 C in the laboratory is equivalent to 90 months of field aging.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, in coastal regions where wetting is often constant, the loss of hydrophobicity occurs very rapidly. In other regions the loss of hydrophobicity is accelerated by acid-rain which often causes depolymerization of the RTV coatings [3,4]. The definition of acid rain is not very clear; generally rainwater having a pH below 5.6 is called acid-rain.…”
Section: Introductionmentioning
confidence: 99%
“…Various rates of aging have been reported in different types of acids and a variation in pH between 2 and 5.6 has been used for this purpose [4][5][6][7][8][9][10]. According to field measurements along the Connecticut coast, the acid rain has a pH of 3.9 [5].…”
Section: Acid Immersion Testsmentioning
confidence: 99%
“…In coastal regions where wetting is often constant, the loss of hydrophobicity occurs very rapidly. In other regions the loss of hydrophobicity is accelerated by acid-rain which often causes depolymerization of the RTV coatings [5][6].…”
Section: Introductionmentioning
confidence: 99%